2021
DOI: 10.1021/acsomega.1c02586
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Applications of Boron Nitride Nanotubes in Energy Harvesting, Electronics, and Biomedicine

Abstract: Boron nitride nanotubes (BNNTs) are structurally and mechanically similar to carbon nanotubes (CNTs). In contrast, BNNTs exhibit unique properties for being electrically insulating and optically transparent due to the polarized boron nitride bonds. All these properties have prevented the use of BNNTs for energy harvesting and electronic devices for more than 25 years. During the past few years, researchers have started to demonstrate a series of novel applications of BNNTs based on unique properties not found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
(59 reference statements)
0
17
0
Order By: Relevance
“…The ever-growing importance of green energy production/storage units to reduce the carbon footprint of fossil fuels has motivated researchers to explore new materials to enhance the efficiency of conventional energy technologies [1,2]. Two-dimensional (2D) materials derived from layered structures have shown to be promising candidates for the future generation of energy devices.…”
Section: Introductionmentioning
confidence: 99%
“…The ever-growing importance of green energy production/storage units to reduce the carbon footprint of fossil fuels has motivated researchers to explore new materials to enhance the efficiency of conventional energy technologies [1,2]. Two-dimensional (2D) materials derived from layered structures have shown to be promising candidates for the future generation of energy devices.…”
Section: Introductionmentioning
confidence: 99%
“…In today's nanoscience and technology, SWC-NTs have been found to be used as sensors, LED devices, and photovoltaic and thermal reservoirs [6]. A review of the literature revealed some studies on the large armchair of SWCNTs such as (7,7), (8,8), (10,10), and (12,12) SWCNTs. Some research was also conducted on the ultra-small SWCNTs, such as (3,3) and (4, 4) SWCNTs.…”
Section: Introductionmentioning
confidence: 99%
“…BNNTs show remarkable resistance to oxidation and greater thermal stability; such remarkable features make them excellent candidates in mechanical reinforcement, radiation shielding, transparent bulk composites, etc. [10]. However, both CNTs and BNNTs have some common properties [7], such as high strength, high stiffness, high thermal conductivity, low density, and high length to diameter [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the substitution of boron atoms in BNNTs in contrary to carbon atoms in CNTs, BNNTs offer unique physical and chemical properties significantly different from those of CNTs . The distinctive properties of BNNTs due to the presence of boron atoms in their structural configuration include noncytotoxicity, optical transparency, exceptional electronic insulation, excellent thermal conduction, resistance to thermal oxidation, , and unprecedented neutron shielding for space vehicles in the harsh outer atmosphere . In parallel, BNNTs possess comparable extraordinary mechanical properties to those of analogous CNTs .…”
Section: Introductionmentioning
confidence: 99%